2018
DOI: 10.1002/ajim.22914
|View full text |Cite
|
Sign up to set email alerts
|

Nickel compounds in the workplaces: Occupations and activities involving high‐risk exposures in Italy

Abstract: Background Nickel (Ni) compounds have been classified as carcinogenic to humans. The aim of the study is to evaluate exposures to Ni at workplaces in Italy. Methods Data on Ni compounds were collected from an occupational exposure registry. Statistical analysis was carried out for exposure‐related variables. The number of workers potentially exposed was estimated for selected industrial sectors. Concurrent exposures with other occupational carcinogens were investigated using two‐step cluster analysis. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the present study, the main pattern of co-exposure includes compounds of nickel and hexavalent chromium (22% of all co-exposed workers). The levels and extent of occupational exposure to both hexavalent chromium and nickel compounds have already been analysed in detail on the basis of data recorded in SIREP following a similar methodology 23 , 24 ) . A recent study on the effects of occupational co-exposure to cadmium and lead concluded that this co-exposure, even at low levels, might have an immunomodulatory effect, suggesting a metal-induced pro-inflammatory immune response 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the main pattern of co-exposure includes compounds of nickel and hexavalent chromium (22% of all co-exposed workers). The levels and extent of occupational exposure to both hexavalent chromium and nickel compounds have already been analysed in detail on the basis of data recorded in SIREP following a similar methodology 23 , 24 ) . A recent study on the effects of occupational co-exposure to cadmium and lead concluded that this co-exposure, even at low levels, might have an immunomodulatory effect, suggesting a metal-induced pro-inflammatory immune response 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…More frightening is that epidemiological reports have proved that occupational Ni exposure could lead to a high incidence of nasal and lung cancers [ 8 , 9 ]. As early as 1990, Ni and its compounds were classified as first-class carcinogens to humans by WHO’s International Agency for Research on Cancer (IARC) [ 10 ]. Interestingly, Ni is the essential element for most organisms as well, so it is impossible to avoid its widespread appearance in modern industries such as refining, electroplating, welding, and the production of nickel-cadmium batteries, or even in food people live on such as vegetables, nuts, and chocolate [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%